An Analytical Study of the Commercial Life of the Holy Prophet (ﷺ) and the Islamic Concept of Entrepreneurship - Dr Nisar Mahmood; Dr Ihsanullah Chishti (Journal of Religion and Society, 2025)
This paper includes a close analysis of the Islamic business ethics and contemporary entrepreneurship with reference to the Prophetic Biography (Siyah of the Prophet Muhammad ﷺ). The work confirms that the whole life of the Messenger ﷺ, the commercial surroundings of Makkah, the partnership of mudaraba with Sayyidah Khadijah (RA), the title al-Sadiq al-Amain (the Trustworthy), the ban on hoarding and profiteering, the charged profit margins, the fulfilment of pledges, the written contract, to risk management, is an intact, practical and blessed business model, which is entirely applicable nowadays. The paper will perform comparative analysis of Western capitalism (the only purpose of which is to maximize profits) and Islamic entrepreneurship (the purpose of which is divine pleasure, service to people, and sustainable development). It concludes that the principles based on the Sīrah of the Prophet such as interest-free economy, transparency, social responsibility, and environmental protection are in complete compliance with the modern world needs. The living examples of this SSIR-based model are Islamic banking, the ḥalal industry, green finance and micro finance which stayed strong amid the worldwide financial meltdowns. The last part will provide the practical advice to Muslim traders and youths, importance of the Sīrah of Prophet in business education and trainings, and emphasize the bright future of Islamic entrepreneurship. It is proved that in case Muslim young people should become the Sanyat as their business role model in several decades the world economy will be organized by Muslim businessmen again, who are going to succeed not only in this world but in the Hereafter that is more important. Keywords: Prophetic Biography (Sīrah), Islamic Entrepreneurship, ḥalāl livelihood, mudārabah, al-Ṣādiq al-Amīn, profiteering, fair profit, avoidance of interest (ribā), contracts, risk management, sustainable economy, business ethics, service to humanity, Islamic banking, Muslim traders